2015
DOI: 10.1016/j.clinbiomech.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral total hip replacement patients with symptomatic leg length inequality have abnormal hip biomechanics during walking

Abstract: BackgroundSymptomatic leg length inequality accounts for 8.7% of total hip replacement related claims made against the UK National Health Service Litigation authority. It has not been established whether symptomatic leg length inequality patients following total hip replacement have abnormal hip kinetics during gait.MethodsHip kinetics in 15 unilateral total hip replacement patients with symptomatic leg length inequality during gait was determined through multibody dynamics and compared to 15 native hip health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 51 publications
0
40
0
1
Order By: Relevance
“…The MCII for HROM was 13.3( 12.1˚, 14.8˚). 16.6% (11.0%, 22.8%) subjects attained this MCII (Fig. 4B).…”
Section: Sagittal Plane Dynamic Hip Range Of Motionmentioning
confidence: 86%
See 2 more Smart Citations
“…The MCII for HROM was 13.3( 12.1˚, 14.8˚). 16.6% (11.0%, 22.8%) subjects attained this MCII (Fig. 4B).…”
Section: Sagittal Plane Dynamic Hip Range Of Motionmentioning
confidence: 86%
“…Unfortunately, between 14 and 22% of patients report limitations in walking function and other physical activities, or do not have clinically meaningful functional improvement . Abnormal gait mechanics may be a barrier to full restoration of physical function . In recent reviews, the most consistently reported spatiotemporal, kinematic, and kinetic gait deficits, are, respectively, reduced walking speed, reduced dynamic hip range of motion in the sagittal plane and reduced dynamic abductor function compared to control subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Function can be objectively and specifically characterized using quantitative gait analysis. Many studies have shown that gait mechanics do not fully return to normal after THA . However, work linking gait mechanics to clinical outcomes is still emerging.…”
mentioning
confidence: 99%
“…Many studies have shown that gait mechanics do not fully return to normal after THA. [19][20][21][22][23][24][25][26][27][28][29][30] However, work linking gait mechanics to clinical outcomes is still emerging. We know that higher values of walking speed, 31,32 stride length, 31 dynamic range of motion, and some external moments 33 are related to clinical improvement, but the relationship between gait mechanics and clinical response has not been investigated.…”
mentioning
confidence: 99%